PIDS-BSP annual macroeconometric model for the Philippines: Preliminary estimates and ways forward - Celia M. Reyes; Connie Bayudan-Dacuycuy; Michael Ralph M. Abrigo; Francis Mark A. Quimba; Nicoli Arthur B. Borromeo; Lora Kryz C. Baje; Sylwyn C. Calizo; Zhandra C. Tam; Gabriel I\~nigo M. Hernandez (Philippine Institute for Development Studies (PIDS), 2020)
Given new programs and policies in the Philippines, there is a need to formulate a macroeconometric model (MEM) to gain more insights on how the economy and its sectors are affected. This paper discusses the estimation of an annual MEM that will be used for policy analysis and forecasting with respect to the opportunities and challenges brought about by new developments. The formulation of an annual MEM is useful in assisting major macroeconomic stakeholders such as NEDA and the BSP in their conduct of policy simulations, macroeconomic surveillance, and economic analysis. Given this backdrop, PIDS and BSP have collaborated to estimate an annual MEM, which has four blocks, namely, the real sector, fiscal sector, trade sector, and monetary sector. Using an Autoregressive Distributed Lag model approach, these sectors are modeled separately although the linkages with each other are specified. These sectoral models are then put together and a test on the predictive accuracy of the forecast of the overall model is done. Some ways to further improve the annual MEM are provided.
Keywords: 330; Autoregressive Distributed Lag Model; Macroeconometric Model; National Income Accounting